Mobilization with high‐dose granulocyte colony‐stimulating factor alone at 12 μg/kg twice a day in high‐risk pediatric patients: A retrospective analysis of the experience in a single center. Issue 5 (4th June 2022) - Iriondo, June; Zubicaray, Josune; Sebastián, Elena; González de Pablo, Jesús; González‐Vicent, Marta; Molina, Blanca; López‐Torija, Ivan; Castillo, Ana; Ramírez, Manuel; Madero, Luis; Díaz, Miguel Ángel; Sevilla, Julián
Abstract: Introduction: Mobilization regimes in pediatric patients at high risk for poor mobilization are not standardized across different institutions. We present a retrospective analysis of our experience with a high‐dose granulocyte colony‐stimulating factor (G‐CSF) regime of 12 μg/Kg per body weight (BW) twice a day for 4 days used in high‐risk patients. Material and methods: We report the results of all pediatric patients mobilized with high‐dose G‐CSF between January 1999 and February 2021 in our center. A successful mobilization was defined as a peripheral blood (PB) CD34 + cell count of ≥10 CD34 + cells/μl on the fifth day of mobilization immediately before leukapheresis. A minimum cell yield of ≥2 × 10 6 CD34 + cells/Kg of BW was required for a successful collection. Results: Of the 262 patients included in the analysis, mobilization failure was found in 27 (10.3%). In a univariate analysis, this was associated with age, weight, baseline diagnosis, and having undergone a previous mobilization cycle, the latter being the only factor that remained significantly associated in a multivariate analysis ( P = 0.03). The 54 patients (20.6%) did not reach the minimum required CD34 + cell yield. 50.4% of the patients reported adverse events (AEs) during the mobilization period, and 23 (9.1%) reported 3 or more concomitant AEs. However, all of them were mild and did not affect the mobilization schedule. Conclusions: Although most high‐risk pediatric patients are successfully mobilized with the high‐dose G‐CSF regime, this approach does not salvage all of them and significantly increases the presence of AEs in comparison to standard‐dose regimes.